Oral health and socioeconomic indicators of adolescents living in a region of extreme poverty - Márcia Cançado-Figueiredo; Fernanda Wisniewski; Taiane Correa-Furtado; Jéssica Vaz-Silva; Eduarda Maria Pereira-Silvestre; Ximena Concha-Melgar (Universidad de Antioquia, 2018)
Introduction: Adolescence is a stage of life in which future hygiene habits are consolidated and is also a period of multiple discoveries and changes in human beings' life. As teenagers go through so many different new emotions, they often leave their health unattended, and thus are at greater risk of suffering oral diseases, which often affect this population early and are treated in late stages, resulting in tooth loss. The aim of this study was to evaluate the oral health profile of adolescents living in a region of extreme poverty. Methods: a cross-sectional analytical study assessing data from 205 adolescents living in the Augusta Meneguine district in the city of Viamão, Rio Grande do Sul, Brazil. Results: The average tooth loss was one tooth per teenager. The Student t-test (p ≤ 0.05) showed no significant differences by sex (p = 0.158). Adolescents whose families had a monthly income of up to one minimum wage had a higher average score of tooth loss, compared to those from families of higher monthly income, but this difference was not significant (p = 0.341). No significant differences were observed between lost teeth and sugar consumption (p = 0.869), nor in relation to the average number of cavities among adolescents with oral hygiene supervision (p = 0.631). Conclusions: This study helped identify poor oral health conditions and low socioeconomic levels among adolescents with low income and education levels, leading them to have high rates of visible plaque, gingival bleeding, caries, and tooth loss.